2015
DOI: 10.1590/s0004-28032015000500004
|View full text |Cite|
|
Sign up to set email alerts
|

Intensive care management of patients with liver disease: proceedings of a single-topic conference sponsored by the Brazilian Society of Hepatology

Abstract: Survival rates of critically ill patients with liver disease has sharply increased in recent years due to several improvements in the management of decompensated cirrhosis and acute liver failure. This is ascribed to the incorporation of evidence-based strategies from clinical trials aiming to reduce mortality. In order to discuss the cutting-edge evidence regarding critical care of patients with liver disease, a joint single topic conference was recently sponsored by the Brazilian Society of Hepatology in coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…The clinical management of patients with HE requires a wide and rigorous differential screening for other causes of encephalopathy and identification of triggers for HE (table 2). Specific therapies for HE (table 3) are often initiated along with treatment of the triggering factors such as gastrointestinal bleeding, toxic medications, electrolyte disorders, and renal dysfunction (table 2) [55]. Cirrhotic patients with HE should have a daily protein intake of 1.2-1.5 g/kg body weight in order to prevent further sarcopenia and thus progress to cachexia.…”
Section: Hepatic Encephalopathymentioning
confidence: 99%
“…The clinical management of patients with HE requires a wide and rigorous differential screening for other causes of encephalopathy and identification of triggers for HE (table 2). Specific therapies for HE (table 3) are often initiated along with treatment of the triggering factors such as gastrointestinal bleeding, toxic medications, electrolyte disorders, and renal dysfunction (table 2) [55]. Cirrhotic patients with HE should have a daily protein intake of 1.2-1.5 g/kg body weight in order to prevent further sarcopenia and thus progress to cachexia.…”
Section: Hepatic Encephalopathymentioning
confidence: 99%
“…We have found that SOFA, CLIF-SOFA, and CLIF-COF scores had a better performance when compared to other general ICU and liver-specific scores, such as APACHE II, CCI, MELD, and its variants and CTP scores in the entire group of patients. SOFA score was previously associated with better prognostication, particularly when compared to MELD and CTP scores, for every patient with cirrhosis in several [9,12,[41][42][43][44] but not all publications [45]. Due to these findings, CLIF-C investigators adapted SOFA score to incorporate INR, instead of platelet count (CLIF-SOFA), to better evaluate liver dysfunction and organ failure (CLIF-C OF) in critically ill cirrhotic patients [26,27,31].…”
Section: Discussionmentioning
confidence: 99%
“…Cirrhotic children can have well-compensated disease with little symptoms or present with decompensated disease, including ascites, encephalopathy, gastrointestinal bleeding, portal hypertension, hepatorenal syndrome, sepsis, dyspnea, nausea, vomiting, jaundice, elongation in prothrombin time, hypotension, pleural effusion, fever, peptic ulcer, chlolelithiasis, renal failure, adrenal failure and hyponatremia [4][5][6].…”
Section: Effects Of End-stage Liver Disease On Pediatric Patientmentioning
confidence: 99%